2008
DOI: 10.1038/ni.1611
|View full text |Cite
|
Sign up to set email alerts
|

Scalable signaling mediated by T cell antigen receptor–CD3 ITAMs ensures effective negative selection and prevents autoimmunity

Abstract: The T cell antigen receptor (TCR)-CD3 complex is unique in having ten cytoplasmic immunoreceptor tyrosine-based activation motifs (ITAMs). The physiological importance of this high TCR ITAM number is unclear. Here we generated 25 groups of mice expressing various combinations of wild-type and mutant ITAMs in TCR-CD3 complexes. Mice with fewer than seven wild-type CD3 ITAMs developed a lethal, multiorgan autoimmune disease caused by a breakdown in central rather than peripheral tolerance. Although there was a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
167
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(187 citation statements)
references
References 49 publications
18
167
1
Order By: Relevance
“…Together, these data suggest that downregulation of CD3z has functional consequences in systemic autoimmunity (23,24). This also agrees with the notion that the strength of the TCR signal is critical for cell lineage fate in T cell development (25), as well as in controlling autoimmunity (26). In this article, we demonstrate that the NOD allele of Cd3z confers impaired T cell activation, resulting in deficient CTLA-4 expression, altered cytokine expression patterns, and reduced proliferation.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Together, these data suggest that downregulation of CD3z has functional consequences in systemic autoimmunity (23,24). This also agrees with the notion that the strength of the TCR signal is critical for cell lineage fate in T cell development (25), as well as in controlling autoimmunity (26). In this article, we demonstrate that the NOD allele of Cd3z confers impaired T cell activation, resulting in deficient CTLA-4 expression, altered cytokine expression patterns, and reduced proliferation.…”
supporting
confidence: 89%
“…It is well established that defective CD3z function leads to impaired activation of T cells upon engagement of the TCR (33,34). Moreover, mutations in different molecules of the TCR/CD3 signaling pathways affect the lineage-commitment decisions during T cell development (25), as well as the development of autoimmunity (26). In line with this, defects in CD3z expression/ function were suggested to have implications for the development of human autoimmune phenotypes (24,35,36).…”
Section: Discussionmentioning
confidence: 95%
“…To discriminate between these models, we used a dimerization reporter system based on the knowledge that erythropoietin receptor (EPOR) signaling, via the Jak-Stat pathway when two signaling domains are in juxtaposition (22), can drive BaF3 cell proliferation (23). A construct was generated that encoded the CD3γ, δ, ε, and ζ subunits, up to the first five intracellular residues, using the 2A cleavage system (24). The ITAMs were removed to eliminate signaling by these motifs.…”
Section: Resultsmentioning
confidence: 99%
“…The truncated CD3 construct (pP2-CD3T2) was generated using 2A cleavage peptides similar to ref. 24. Sequence encoding CD3δ(aa:1-132)-GSG-F2A-CD3γ(aa:1-143)-RSGG-T2A-CD3ε(aa:1-139)-GSG-P2A-CD3ζ(aa:1-57)-stop was cloned into the MSCV-based vector pP2-MSCV (puromycin resistance).…”
Section: Methodsmentioning
confidence: 99%
“…140). Conforming to the models described in this Review, they found that minor loss of signalling capacity (9-7 ITAMs) was compensated for, extreme loss of signalling (0-1 ITAMs) resulted in profound immunodeficiency, and an intermediate level of signalling capacity (6-2 ITAMs) resulted in the dual presentation of partial immunodeficiency and autoimmunity 140 .…”
Section: Note Added In Proofmentioning
confidence: 99%